Doença do disco intervertebral em cães - (:unkn) unknown (Universidade Camilo Castelo Branco, 2017)
A herniated disc is defined as a complete or partial dislocation of the intervertebral disc, which usually causes spinal cord injury. Very common condition in dogs, especially chondrodistrophic. Diagnosis is based on history, clinical signs and thorough neurological examination for the location of the lesion. After the suspicious site, are indicated from simple radiographs, cervical or lumbar pyelography or CT scan. The alterations in the intervertebral disc range from chondroid metamorphosis (extrusion) or fibroid (protrusion). Depending on the compression degree and location, the signals may vary from mild ataxia to quadriplegia. You can affect the cervical, thoracolumbar and lumbar spine. Treatment options consist of medical and / or surgical treatment and is related to the stage of the disease and the degree of urgency. Early diagnosis and treatment are critical for recovery from these injuries.
Keywords: Hérnia de disco; Cães; Tratamento; CA